Measurement Instruments in Cross-National Surveys (Version 2.0) - Behr, Dorothée,Braun, Michael,Dorer, Brita (online, 2016)
Abstract: This contribution deals with measurement instruments - that is, questionnaires and individual items - employed in international survey research. By international surveys we mean cross-national comparative studies whose concept, implementation, and organisation are shaped by the comparability requirement. We begin by focussing on general aspects of the comparability of international surveys. In the case of problems that occur in all surveys - for example sampling-related problems and nonresponse - we refer the reader to the corresponding thematic contributions in the Survey Guidelines and to the literature. We make a distinction between ensuring the comparability of measurement instruments ex-ante and ex-post - that is, before or after the actual survey is, or has been, conducted. Comparability is established ex ante by means of pretests, for example; it is established ex post within the framework of the data analysis or additional studies. We focus in particular on question transla
10.15465/gesis-sg_en_006
Keywords: (thesoz)Fragebogen; (thesoz)interkultureller Vergleich; (thesoz)Übersetzung; (thesoz)Messinstrument; (thesoz)Pretest; (thesoz)Qualität; (thesoz)Datengewinnung; (thesoz)Stichprobe; (thesoz)Umfrageforschung